Potencial de mitigação de gases de efeito estufa (GEE) através do sistema de integração-lavoura-pecuária-floresta (ILPF), uma revisão - Noernberg, Rebeca Rodrigues (Universidade Federal de São Carlos, 2023)
The emission of greenhouse gases (GHG) generates great concern worldwide due to its high impact on humanity, increasing the negative impacts of global warming, and thus, a higher incidence of extreme weather events. In 2020, emissions from the agricultural sector totaled 577 million tons of CO2 equivalent, an increase of 2.5% compared to the previous year (562.9 million). With this new reality, it is extremely important to identify and adopt new production systems that can contribute to more sustainable agricultural production, such as the crop livestock integration system (CLFI), helping to capture CO2 from the atmosphere, and contributing to the adoption more adapted and resilient productive systems. The main focus is the integrated crop, livestock, forest (CLFI) system and the main technologies that are used to neutralize greenhouse gases (GHG). Therefore, the importance of integrated systems for the sustainability of agriculture and livestock is defined; integration systems are conceptualized, reviewing the potential for carbon sequestration in soil and biomass in CLFI systems. In addition, the agronomic, environmental and social benefits of the integrated systems were highlighted, as well as the importance of technical assistance, and of government plans to encourage the increase in areas and the identification of obstacles to the increase in areas so that it can achieve the objective of mitigating emissions of (GHG).
Potential for mitigating greenhouse gases (GHG) through the crop-livestock-forest integration system (CLFIS): a review
Keywords: Sustentabilidade na agricultura; Produção integrada; Efeito estufa; Sequestro de carbono; Sequestro de carbono na biomassa; Plano ABC+; CIENCIAS AGRARIAS